The Heterogeneous Impact of Pension Income on Elderly Living Arrangements: Evidence from China's New Rural Pension Scheme - Lingguo Cheng; Hong Liu; Ye Zhang; Zhong Zhao (Institute for the Study of Labor (IZA), 2015)
This paper investigates the impact of pension income on living arrangements of the elderly. Taking advantage of a unique opportunity due to the recent establishment and expansion of the social pension system in rural China, we explicitly address the endogeneity of pension status and income through a fixed-effect model with instrumental variable approach by exploiting exogenous time variation in the program implementation at county level. We find an overall positive effect of pension income on independent living as well as considerable heterogeneity. The elderly with easy access to their adult children, possessing higher financial capacity, in less long-term care and psychological need, and having more education are more likely to live independently after receiving pension income. Our results confirm that independent living is a normal good, but highlight that living arrangement is multidimensional in rural China.
Keywords: J12; H55; I38; 330; pension income; living arrangements; heterogeneity; China